Empowering students’ personal recount writing and motivation to write through self-regulated strategy development model - Uli Fauziyah Miatin; Pangesti Wiedarti (Journal of Education and Learning (EduLearn), 2019)
This article reports a study of results of Self-Regulated Strategy Development (SRSD) model on the teaching of English writing, particularly on students’ personal recount writing and their motivation to write. The study was aimed at investigating whether: 1) SRSD was effective toward students’ personal recount writing and 2) SRSD was effective toward students’ writing motivation. A quasi-experimental research in the form of pre-test posttest control group design was applied in the study. To date, second year students in a junior high school in Kebumen, Central Java, Indonesia were used as the participants of the study. There were 60 students participated in the study whereby 30 of them were assigned into the experimental group received the SRSD model; and another 30 students were administered into the control group with the conventional teaching model. Results on MANCOVA show that students’ writing performance in the experimental group was significantly higher than that of the control group with p=0.017 while students’ writing motivation in the experimental group was insignificantly higher compared with the control group with p=0.104. This indicates that although SRSD was effective toward students’ personal recount writing, its effectiveness couldn’t be followed by students’ writing motivation.